2012
DOI: 10.1080/09585192.2012.661990
|View full text |Cite
|
Sign up to set email alerts
|

Financial participation in Finland: incidence and determinants

Abstract: Abstract:We provide the first comprehensive analysis of financial participation in Finnish manufacturing companies. Compared to many developed economies, the incidence of profit sharing in Finland is found to be relatively high. Cash-based profitsharing (CPS) schemes are the most commonly used method of financial participation, and around 40% of manufacturing companies had them in 2005. Share-based schemes and personnel funds are much less common. Moreover, CPS schemes were growing fast in the early 2000s, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…It can be argued that there is as much variety within national archetypes as between them (Walker et al, 2014). Internal firm dynamics and ownership characteristics might have a stronger effect than national setting in determining the relative use of financial incentives (Kolb, 2012;Jones et al, 2012). Firms may have 'space' even within national institutional frameworks to make real strategic choices according to variations in firm characteristics (Poutsma et al, 2012(Poutsma et al, : 1513.…”
Section: Co-determination and Contingent Paymentioning
confidence: 99%
“…It can be argued that there is as much variety within national archetypes as between them (Walker et al, 2014). Internal firm dynamics and ownership characteristics might have a stronger effect than national setting in determining the relative use of financial incentives (Kolb, 2012;Jones et al, 2012). Firms may have 'space' even within national institutional frameworks to make real strategic choices according to variations in firm characteristics (Poutsma et al, 2012(Poutsma et al, : 1513.…”
Section: Co-determination and Contingent Paymentioning
confidence: 99%
“…Studies have shown that the adoption of EO was determined by various factors, such as the following: industry risk, employee total wealth, years of education, length of service (Brickley, 1991), suboptimal financial performance, capital to labor ratio, employment growth rate (Jones & Kato, 1993), management-employee relationship (Beaumont, 1995), productivity-and flexibility-related factors (Kruse, 2010), information coordination, work incentive, asset specificity, finance and investment, institutional factors (Ben-Ner, Burns, Dow, & Putterman, 2000), growth potential, times interest earned, firm scale (Ding & Sun, 2001), and the firm's stockholding ownership structure (Jones, Kalmi, Kato, & Makinen, 2012). Especially, Ben-Ner et al (2000) proposed that for EO that emphasizes return rights, the length of service and wage level are the main determinants, while for EO that emphasizes control rights and the job complexity is a major determinant.…”
Section: Overall Effect Of Employee Ownership On Firm Performancementioning
confidence: 99%
“…PRP is broader than just profit sharing because the level of measured performance can vary and since it does not need to include profitability. An analysis of the PRP schemes studied in Jones, Kalmi, Kato, and Mäkinen (2012), however, revealed that they usually (for white-collar schemes, almost always) include profitability as a performance criterion and are typically broad-based (covering at least 50% of all employees), and a large majority actually include all employees. The PRPs in our sample are group-based incentive schemes, and most can be classified as cash-based profit sharing following the typology of Poutsma and de Nijs (2003).…”
Section: Data and Empirical Strategymentioning
confidence: 99%
“…While most stock option schemes in Finland are selective (Jones, Kalmi, and Mäkinen 2006), we include only broad-based stock option schemes here. Similarly, we include broad-based share ownership schemes, though direct share ownership (other than through personnel funds) is uncommon in Finland (Jones et al 2012). To measure broad-based share ownership and stock option schemes, as in previous studies (e.g., Kruse et al 2010), the proportion of employees is at least 50%.…”
Section: Data and Empirical Strategymentioning
confidence: 99%